Are trampling effects by wild tundra reindeer understudied? - Heggenes, Jan; Odland, Arvid; Bjerketvedt, Dag K. (Rangifer, 2018)
Grazing and trampling by the wide-ranging wild tundra reindeer may have major top down landscape effects by causing vegetation changes. Grazing, as the collective effect of eating, trampling, defecation, and urination, has been studied extensively. In contrast, trampling effects per se are rarely studied, and almost never quantified, even though considered very important. The main reason appears to be methodological; effects of trampling imprints are difficult to measure and quantify systematically. In particular, in winter reindeer may largely subsist on slow-growing ground lichens. They grow in habitats with little snow cover and extensive soil frost, and dry lichen may be particularly susceptible to trampling, generating a likely substantial forage loss.